Pahang River community satisfaction towards their quality of life: the case of community in Pekan, Pahang - Mohamed Shaffril, Hayrol Azril; Md. Yassin, Sulaiman; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (Canadian Center of Science and Education, 2011)
We examined the satisfaction of Pahang River community who live in Pekan towards certain aspects of their quality of life. What is the level of satisfaction of this community towards their quality of life; low, moderate or high? This is a quantitative study where questionnaire was used to gain the data needed. A total of 300 villagers had been selected as the respondents for this study. All of the respondents selected were the villagers that live along Pahang River in the area of Pekan, Pahang. SPPS was used to run the appropriate analyses. Overall, our analyses revealed that the Pahang River community living in Pekan have a moderate satisfaction towards their quality of life. However, further analysis employed, have indicated that Pahang River community in Pekan do have a high level of satisfaction towards four aspects of quality of life namely social involvement and relationship, safety at areas, home condition and education. Development in Pekan which includes the improvements along Pahang River need to continuously take place as it can have a huge impact on the Pekan community especially those who live along the Pahang River.